Problem Muallaf Tionghoa Bangka Pasca Konversi Agama - Al Fakhri Zakirman; Musa Musa; M. Sholeh Marsudi (Pascasarjana IAIN Metro, 2023)
This paper describes the problems faced by Chinese converts in Bangka after conversion to Islam. Departing from the strong relationship between the ethnic Chinese and Malays in Bangka, it affected the condition of Chinese converts in Bangka. At least they are still treated well by their family of origin. This article discusses the problems faced by Chinese converts in Bangka and how to solve each problem they face. This field research is qualitative by collecting data through interviews and observations. Based on the author's study, the problems faced by Chinese converts in Bangka can be summarized into four things: first; the problem of understanding and practicing religion, secondly; the problem of economic independence, third; adaptation problems with local Muslims, fourth is the issue of support from converts organizations, Islamic organizations and the government in this case the Ministry of Religion.